Efficient transformation of L-lactide into alkyl lactyllactate and alkyl lactate via alcoholysis reaction catalyzed by in-situ-activated calcium oxide - Hemmarat Kreethatorn (2018)
© 2016 Elsevier B.V. Catalytic behavior of CaO on the alcoholysis of L-lactide to alkyl lactyllactate and alkyl lactate was investigated. CaO catalyst exhibited an excellent alcoholysis activity with methanol; and the activity was lessened for larger alcohols, following the trend for the acidity of the hydroxyl proton. A mixture of alkyl lactyllactate and alkyl lactate was obtained at total conversion; but the product ratio was tunable by controlling reaction time. In addition, CaO could be reused for at least six times with an unexpected increase in the activity after the first run. The structural and morphological studies revealed that the in situ activation of CaO by ester products was the key factor to this enhanced activity.